Stereotactic Radiosurgery for Intraventricular Metastases: A Multicenter Study. Issue 3 (7th March 2023) - Mantziaris, Georgios; Pikis, Stylianos; Xu, Zhiyuan; Mullen, Reed; Alzate, Juan; Bernstein, Kenneth; Kondziolka, Douglas; Wei, Zhishuo; Niranjan, Ajay; Lunsford, L. Dade; Liscak, Roman; May, Jaromir; et al.
Abstract : BACKGROUND: Intraventricular metastases (IVMs) are uncommon, and their optimal management remains debatable. OBJECTIVE: To define the safety and efficacy of stereotactic radiosurgery (SRS) in the treatment of IVMs. METHODS: This retrospective, multicenter study included patients managed with SRS for IVMs. SRS-induced adverse events, local tumor or intracranial progression, and the frequency of new-onset hydrocephalus or leptomeningeal spread were documented. Analyses of variables related to patient neuroimaging or clinical outcomes were also performed. RESULTS: The cohort included 160 patients from 11 centers who underwent SRS for treatment of 1045 intracranial metastases, of which 196 were IVMs. The median survival from SRS was 10 months. Of the 154 patients and 190 IVMs with imaging follow-up, 94 patients (61%) experienced distant intracranial disease progression and 16 IVMs (8.4%) progressed locally. The 12- and 24-month local IVM control rates were 91.4% and 86.1%, respectively. Sixteen (10%) and 27 (17.5%) patients developed hydrocephalus and leptomeningeal dissemination post-SRS, respectively. Adverse radiation effects were documented in 24 patients (15%). Eleven patients (6.9%) died because of intracranial disease progression. CONCLUSION: SRS is an effective treatment option for IVMs, with a local IVM control rate comparable with SRS for parenchymal brain metastases. Leptomeningeal spread and hydrocephalus in patients with IVM occur in a minority of patients, but these patients warrant careful follow-up to detect these changes.